NMR evaluation of apple cubes and apple juice composition subjected to two cold plasma technologies. (October 2021) - Farias, Thayane R.B.; Alves Filho, Elenilson G.; Silva, Lorena M.A.; De Brito, Edy S.; Rodrigues, Sueli; Fernandes, Fabiano A.N.
Abstract: This study evaluated the effects of two cold plasma technologies, glow discharge plasma and dielectric barrier discharge plasma (DBD), on the chemical composition of apple cubes and apple juice analyzed by 1 H NMR coupled with chemometrics. The effects of different technologies (glow discharge and DBD) and operating conditions (processing time, gas flowrate, and excitation frequency) were evaluated on the concentration of sugars and organic acids of apple juice and apple cubes. Changes in sugars and organic acids were observed after the application of both plasma technologies. Glow discharge plasma application induced the decrease in sucrose content and the increase in glucose, fructose, and malic acid. Dielectric barrier discharge plasma induced sugar reduction and increased malic acid content. Cold plasma technology depolymerized sucrose into glucose and fructose by cleavage at the ether bond. DBD plasma further induced glucose and fructose consumption, most probably through the phenylpropanoid mechanism. Cold plasma technology could be used to modulate apple products' sensory characteristics, altering both sweetness and sugar-acid ratios. Highlights: Two cold plasma technologies were compared. Cold plasma induced changes in sugars and organic acids composition. Glow discharge plasma increased the sweetness of apple products. Dielectric barrier discharge plasma reduced the sweetness of apple products. Both technologies decreased the sugar-acid ratio of apple products.